Perspectives of Interfaith Figures on Religious Moderation in an "Intolerant City": A Study in Padang - Halim, Ismail; Faisal, Faisal (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
This study aims to examine the perspectives of interfaith leaders in Padang City on religious moderation. This study uses a naturalistic qualitative approach, with data collection techniques of in-depth interviews with Muslim, Catholic, Christian, Hindu, Buddhist and Confucian religious leaders. This study focuses on four pillars or indicators of religious moderation, namely commitment to nation and state, tolerance, non-violence, and accommodation to local culture. The results found that interfaith leaders in Padang City strongly support the concept of religious moderation because religious moderation is believed to be relevant to the teachings of each religion, such as the common ideals of building the life of the nation and state for mutual progress, living in harmony amid differences, rejecting acts of violence in the name of religion, and maintaining and respecting local culture. This study also found that interfaith leaders as religious elites spread the values of religious moderation to each of their followers. The interfaith leaders also agreed that Padang City is conducive in terms of interfaith relations, even though the city is ranked low in the tolerance index by a number of research institutions